Pendampingan PHBS Dengan Pelatihan Cara Menggosok Gigi dan Mencuci Tangan yang Benar di TK Aisyiyah Bustanul Athfal Gombang dengan Pemanfaatan Media Edukasi - Rahmi Nurhaini; Astri Wahyuningsih; Risma Nanda; Rita Nurjanah; Rizqi Rahmawati; Sarmini Sarmini; Shafa Andhanie; Ulfah Fauziyyah (Universitas Muhammadiyah Klaten, 2024)
Clean and healthy living habits (PHBS) are critical in maintaining the health of early childhood. Aisyiyah Bustanul Athfal Gombang Kindergarten requires assistance in implementing PHBS, especially regarding proper tooth brushing and handwashing techniques. This activity aims to increase children’s awareness and knowledge of personal hygiene to prevent diseases. The activity utilized interactive training with educational media such as puzzles, posters, leaflets, videos, and live demonstrations. Children actively participated in direct practice sessions, enhancing their understanding and motivation to apply PHBS daily. The results indicated an improvement in children's knowledge and skills in personal hygiene, particularly in brushing teeth and washing hands. This program contributes to fostering healthy living habits from an early age.